ASSISTANCE OF MSMES THROUGH PACKAGING AND MARKETING TRAINING BOTH ONLINE AND OFFLINE PEANUT PRODUCTS UMPET FLAVOR VARIANTS BECOME A COMPETITIVE PRODUCT IN SUKASARI VILLAGE: PENDAMPINGAN UMKM MELALUI PELATIHAN PENGEMASAN DAN PEMASARAN BAIK ONLINE MAUPUN OFFLINE PRODUK KACANG UMPET VARIAN RASA MENJADI PRODUK YANG KOMPETITIF DI DESA SUKASARI - Ombi Romli; Arta Rusidarma Putra (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
One of the duties of a lecturer is to perform a tri dharma of universities by carrying out community service activities. Community service activities are actually to improve the ability of citizens in the management, especially in the process of product packaging and marketing of umkm products, especially bean umpets that have variants of flavor. 1) This training starts from the manufacture of packaging, packaging loga, to packing according to standards and not forgetting from the marketing side we train especially marketing by using social media as well as the participants are proficient in running it, (2) Improving the welfare of the para through the improvement of skills obtained in this training so that every economic actor can improve his business results through modern packaging and extensive marketing through social media. The achievement of the training objectives is done through lecture methods as a theory, then mentoring, demonstration, exercises (tutorials), and Q&A. After the training activities are carried out monitoring or evaluation by the committee (lecturers and students) to see the progress of their business progress or not. Based on the questionnaire results from some residents who were participants, the training of packaging and marketing of peanut products online and offline community service is running lancer by the expected target. This training program can provide skills in making competitive product packaging and do product marketing, especially online through social media, both Facebook media, what up, and others. Obstacles that arise at the training stage can be overcome well through mentoring methods. Criticism and suggestions can be submitted from the results of this community service program, for the participants are expected to have the spirit and motivation in developing the business of bean umpet. For education, practitioners are expected always to be able to help and accompany the participants who have a business of bean umpet in sukasari village both theory and practice so that the need continues to grow and develop. For lppm campus through community service (P2M) should always motivate and become a facilitator of the service program in order to continue to run and develop as it should